2015
DOI: 10.1007/s10943-015-0127-1
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden, Spirituality, and Psychological Well-Being of Parents Having Children with Thalassemia

Abstract: The research determined the relationship of caregiving burden, spirituality and psychological well-being of parents of Pakistani thalassemic patients in a crosssectional research design. The sociodemographic form, Montgomery-Borgatta burden measure (Montgomery et al. in Who should care for the elderly? An east-west value divide. World Scientific, River Edge, pp 27-54, 2000), Multidimensional Measure of Islamic Spirituality (Dasti and Sitwat in J Muslim Ment Health 8(2):47-67, 2014. doi: 10.3998/jmmh.10381607.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 26 publications
2
26
0
2
Order By: Relevance
“…Fourth, the present study considered SWB as the outcome variable, and adopted Diener’s (1984) model of SWB containing positive affect, negative affect, and life satisfaction to measure SWB because of its wide acceptance and well-established generalizability. However, it is suggested that for better understanding of multi-facet constructs of well-being and its relations to character strengths and strengths use as well as future self-continuity, future research should adopt some other models of well-being such as Ryff’s (1989) model of PWB and Seligman’s (2011) PERMA of well-being. Finally, given that this was the original study to present the moderating role of future self-continuity, future research should further investigate whether there are more underlying mechanisms (or other psychological or behavior variables such as goals pursuit and mental imagery) in such relations, which would provide more specific evidence to elucidate the role of future self-continuity in relation to strengths use and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the present study considered SWB as the outcome variable, and adopted Diener’s (1984) model of SWB containing positive affect, negative affect, and life satisfaction to measure SWB because of its wide acceptance and well-established generalizability. However, it is suggested that for better understanding of multi-facet constructs of well-being and its relations to character strengths and strengths use as well as future self-continuity, future research should adopt some other models of well-being such as Ryff’s (1989) model of PWB and Seligman’s (2011) PERMA of well-being. Finally, given that this was the original study to present the moderating role of future self-continuity, future research should further investigate whether there are more underlying mechanisms (or other psychological or behavior variables such as goals pursuit and mental imagery) in such relations, which would provide more specific evidence to elucidate the role of future self-continuity in relation to strengths use and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study that investigated the relationship between spiritual beliefs and caregiver burden in caregivers of terminally ill patients with cancer. Recently, a Pakistani study investigated the relationship between the burden of caregivers, spiritual and psychological well‐being in Islamic parents of thalassemia patients (Anum & Dasti, ); the results of this study showed that two domains of spirituality (self‐discipline and meanness‐generosity) mediated the relationship between caregiver burden and psychological well‐being of caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been explored by many researchers (Anum & Dasti, 2016) that patients and families of thalassemia are usually pilloried, particularly because of tribal factors. Mostly these individuals (patients of thalassemia disease) are called and pronounced as thalassemic (being labeled based on their disease).…”
Section: Theoretical Construction Of Beta Thalassemia Majormentioning
confidence: 99%